Insulin glargine - Upadhyay, DK; Palaian, S; Prabhu, M; Shankar, PR; Mishra, P (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Insulin glargine is a long-acting human insulin analog prepared using recombinant DNA technology. It is the first long-acting analog of human insulin to be approved for clinical use. It is administered once daily and has a smooth 24 hour time-action profile that provides effective glycemic control with minimal risk of hypoglycemia. It may be used for children who are 6 years or older. Though the risk for developing hypoglycemia is less, hypoglycemia is still the most commonly reported adverse effect, especially within the first four weeks of therapy after a switching over to insulin glargine. Intravenous administration of this drug is not recommended due to the risk of severe hypoglycemia. The patients prescribed insulin glargine should be thoroughly counseled by the healthcare professionals regarding its safe and effective use. The vials and cartridges of insulin glargine should be stored in a refrigerator between 2 to 8 degrees C. Keywords: Glargine, Hypoglycemia, Insulin. Journal of Institute of Medicine, April, 2008; 30:1 72-77 The full text of this paper is available from the Journal of Institute of Medicine website